The Economic Burden of Burnout - Arash Nekoei; Jósef Sigurdsson; Dominik Wehr (CESifo GmbH, 2024)
We study the economic consequences of stress-related occupational illnesses (burnout) using Swedish administrative data. Using a mover design, we find that high-burnout firms and stressful occupations universally raise burnout risk yet disproportionately impact low-stress-tolerance workers. Workers who burn out endure permanent earnings losses regardless of gender—while women are three times more susceptible. Repercussions of burnout extend to the worker's family, reducing spousal income and children's educational achievements. Through sick leaves, earnings scars, and spillovers, burnout reduced the national labor income by 2.3% in 2019. We demonstrate how estimated costs, combined with a prediction model incorporating workers' self-reported stress, can improve the design of prevention programs.
Keywords: E24; J21; J28; I18; 330; amenities; mental health; employment; misallocation; fiscal cost